2019
DOI: 10.1038/s41438-018-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated multiple gene editing in Brassica oleracea var. capitata using the endogenous tRNA-processing system

Abstract: Cabbage (Brassica oleracea var. capitata) is a biennial plant with strong self-incompatibility and an obligate requirement for prolonged vernalization by exposure to low temperatures to induce flowering. These characteristics significantly increase the difficulty of exploiting novel germplasm induced by physical or chemical mutagens. In this study, we report a CRISPR/Cas9 gene-editing system based on endogenous tRNA processing to induce high efficiency and inheritable mutagenesis in cabbage. Using the phytoene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Traditional genetic crossing/breeding approaches to obtain higher order mutants, however, are both time-consuming and complicated by genetic linkage. Compared to traditional breeding, CRISPR-Cas9 gene editing has been recently used to study redundant gene families in several plant species such as rice, wheat, cabbage, tomato and Arabidopsis [21,[26][27][28][29]. The research reported here, however, represents the first application of CRISPR/Cas9 to understand GTs families in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional genetic crossing/breeding approaches to obtain higher order mutants, however, are both time-consuming and complicated by genetic linkage. Compared to traditional breeding, CRISPR-Cas9 gene editing has been recently used to study redundant gene families in several plant species such as rice, wheat, cabbage, tomato and Arabidopsis [21,[26][27][28][29]. The research reported here, however, represents the first application of CRISPR/Cas9 to understand GTs families in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9 enables precise modification of genomic sequences and the ability to regulate gene expression patterns (Mahfouz et al 2014). The application of CRISPR/ Cas9 has been increasing in plants (Liu et al 2019b;Ma et al 2019;Zhang et al 2019b). Liu et al (2019b) used the CRISPR/Cas9 genome-editing system based on RNA endoribonuclease Csy4 processing to induce high-efficiency and inheritable targeted deletion of genes (AP1, SVP, and TFL1) involved in floral development in A. thaliana.…”
Section: Discussion and Future Objectivesmentioning
confidence: 99%
“…Zhang et al (2019b) used the CRISPR/Cas9 system to achieve efficient mutagenesis of five wheat genes, confirming that CRISPR/Cas9-induced gene editing plays important roles in wheat genome engineering through Agrobacteriummediated transformation. Based on the CRISPR/Cas9 gene editing system, Ma et al (2019) achieved trait stacking in cabbage (Brassica oleracea) with the phytoene desaturase gene BoPDS, the S-receptor kinase gene BoSRK and the male-sterility-related gene BoMS1 as target genes. This confirmed that CRISPR/CAS9 is an efficient tool for studying gene function.…”
Section: Discussion and Future Objectivesmentioning
confidence: 99%
“…Notably, the quickly emerging gene-editing technique helps realize accurate alteration of the target DNA sequence. Ma et al 172 applied CRISPR/Cas9-mediated multiple gene editing in cabbage, with the targets BoPDS, BoSRK, and BoMS1, and successfully generated albino, self-compatible, and male sterile lines, showing its great power in improving plant traits.…”
Section: Creating Novel Germplasms Via Close or Distant Hybridizationmentioning
confidence: 99%
“…f Pyramiding both the qualitative and quantitative R loci generates durable BL resistance in B. napus74 . g CRISPR/Cas9based gene editing helps knockout multiple target genes in B. oleracea172 . h Expressing the CP gene from TuMV confers high resistance in B. napus200…”
mentioning
confidence: 99%